2004
DOI: 10.1373/clinchem.2004.037788
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase and Superoxide Dismutase Gene Polymorphisms and Noise-Induced Hearing Loss

Abstract: Background: Noise-induced cochlear epithelium damage can cause hearing loss in industrial workers. In experimental systems, noise induces the release of free radicals and may damage the cochlear sensorial epithelium. Therefore, genes involved in regulating the reactive oxygen species manganese-superoxide dismutase (SOD2) and the antioxidant paraoxonase (PON) could influence cochlea vulnerability to noise. We evaluated whether susceptibility to noise-induced hearing loss (NIHL) is associated with SOD2, PON1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 36 publications
(34 reference statements)
2
68
1
4
Order By: Relevance
“…[13] However, no study has examined the serum PON levels of patients with ISSHL. We found no significant difference between the pretreatment serum anti-HSP70 levels of the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] However, no study has examined the serum PON levels of patients with ISSHL. We found no significant difference between the pretreatment serum anti-HSP70 levels of the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[7][8][9][10][11][12] One study found an association between a PON2 gene polymorphism and SHL and postulated that it could represent a marker of susceptibility to noise-induced hearing loss. [13] As mentioned, few studies have evaluated the relationship between anti-HSP70 levels and the prognosis of ISSHL patients. In addition, no study has directly investigated the correlation between serum PON activity and hearing loss.…”
mentioning
confidence: 99%
“…Male workers from an aircraft factory were enrolled a study in which SOD polymorphism was studied. 24 Even if there was some obstacles like small sample size and the difficulty in matching cases to controls, the data suggest Mn-SOD (SOD2) polymorphism could predispose to noiseinduced hearing loss. The other study was conducted by Chang et al in which the distribution of Mn-SOD genetic polymorphisms IVS3-23T/G on noise susceptibility in Asians were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired function of antioxidant enzymes caused by genetic variation has been postulated as leading to failure of cellular responses against the toxic effects of ROS and subsequent peroxidative cell injury. Studies of knock-out models of Gpx1 and Sod1 have shown that deletion in the two antioxidant genes can lead to both age-related and noise-induced HL [51][52][53]. These mice show the phenotypic characteristics of ARHL.…”
Section: Oxidative Stressmentioning
confidence: 99%